Prediction of minimum chip thickness in tool based micro end milling - Ali, Mohammad Yeakub; Khan, Ahsan Ali; Mohamad Asharaf, Asfana Banu; Abdul Wahab, Adibah (Penerbit Universiti Tun Husseion Onn, 2012)
This paper presents the analysis and modelling of minimum chip thickness by tool based micro end milling with control parameter of cutting speed, feed rate, and depth of cut. The formed chip thickness was measured using scanning electron microscope The data were analyzed and an empirical model is developed. The optimum value for the minimum chip thickness was 375 nm with cutting speed of 2275 rpm, feed rate of 2.6 mm/min, and depth of cut 0.6 μm using Ø 0.8 mm tool. The analysis revealed that the depth of cut is the most influential parameter on the minimum chip thickness. The investigation was performed on poly methyl methacrylate (PMMA) using integrated multi-process micro machine tools DT 110. The minimum chip thickness is found to be important to avoid tool breakage, deterioration of surface finish and to increase the tool life.